Absolute Liability: Legal Responsibility of Fund Transfer Providers in the Event of Errors: Tanggung Jawab Mutlak: Tanggung Jawab Hukum Penyedia Layanan Transfer Dana Jika Terjadi Kesalahan - Putra, Wildan Revandra; Multazam, M Tanzil (Universitas Muhammadiyah Sidoarjo, 2022)
This article presents a study on the legal responsibility of fund transfer providers, particularly banks, in cases of errors in fund transfers. The goal of this research is to describe and explain the legal cover for bank customers who use fund transfer services, based on Law Number 3 of 2011 concerning Funds Transfer. The research method used is normative or doctrinal, with data collected through literature review. The results indicate that the legal responsibility for fund transfer providers is absolute and without any possible defense. This study has important implications for bank customers and fund transfer providers, as it clarifies the legal liabilities and responsibilities in the event of fund transfer errors. Highlights: The article focuses on the legal responsibility of fund transfer providers, particularly banks, in cases of errors in fund transfers. The research method used is normative or doctrinal, with data collected through literature review. The results indicate that the legal responsibility for fund transfer providers is absolute and without any possible defense.